2021
DOI: 10.20944/preprints202102.0135.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Estimating Algorithmic Information using Quantum Computing for Genomics Applications

Abstract: Inferring algorithmic structure in data is essential for discovering causal generative models. In this research, we present a quantum computing framework using the circuit model, for estimating algorithmic information metrics. The canonical computation model of the Turing machine is restricted in time and space resources, to make the target metrics computable under realistic assumptions. The universal prior distribution for the automata is obtained as a quantum superposition, which is further conditioned to es… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

4
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…QT roadmaps developed by governments, companies, and consulting firms worldwide anticipate various opportunities, challenges, and risks arising within the next 25 years. Some challenges demand immediate attention, such as establishing practical solutions to protect privacy [109] and ensure information security [110] in light of quantum computing's threat to widely used public key cryptosystems 13 . Other ELSPI of QT may emerge in the longer term, but proactive measures are necessary to guarantee responsible quantum R&D. Previous cycles of technological innovation-including currently AI-teach us that important ELSPI that can emerge in the longer term [72].…”
Section: Conclusion: a Path Forwardmentioning
confidence: 99%
“…QT roadmaps developed by governments, companies, and consulting firms worldwide anticipate various opportunities, challenges, and risks arising within the next 25 years. Some challenges demand immediate attention, such as establishing practical solutions to protect privacy [109] and ensure information security [110] in light of quantum computing's threat to widely used public key cryptosystems 13 . Other ELSPI of QT may emerge in the longer term, but proactive measures are necessary to guarantee responsible quantum R&D. Previous cycles of technological innovation-including currently AI-teach us that important ELSPI that can emerge in the longer term [72].…”
Section: Conclusion: a Path Forwardmentioning
confidence: 99%
“…In [14] a global/objective view is presented, which involves quantum automata for algorithmic information. A framework for causal inference based on algorithmic generative models is developed.…”
Section: Quantum Computation and Algorithmic Informationmentioning
confidence: 99%
“…State of the art development of the QAOA algorithm in practice is shown to be advancing, with a wide variety of algorithms shown for different, but similar problems. While these NP-hard problems are similar, it has been shown that QAOA is not well suited for every problem [54]. In some cases, such as the Ising problem, current classical approximations are expected to perform better and alternatives like the quantum adiabatic algorithm might be a better fit.…”
Section: Conclusion and Future Developmentsmentioning
confidence: 99%